THE ROLE OF ACCOUNT OFFICERS AND LOYALTY TO SAVINGS INTEREST AT KSPPS BMT SURYA RAHARJA SIDAYU - Nabilah, Nabilah Anisatuz Zahroh; Wiwik Saidatur Rolianah (I-Finance Journal, 2025)
This study aims to examine the impact of the role of account officers (X1) and loyalty (X2) on the interest in saving (Y) of members of the BMT Surya Raharja Credit Union, Sidayu branch. The research population consisted of 1,820 active members, with 95 participants selected through purposive sampling. This study used an associative quantitative approach with data collection through a closed questionnaire using a five-point likert scale. Data analysis was performed using SPSS version 25, including validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and F-tests and t-tests. The results of the study show that both partially and simultaneously, the variables of account officers and loyalty have a significant effect on interest in saving. Account officers play an important role through personal communication, responsive service, and Islamic financial education, while loyalty programs increase member engagement through rewards and incentives. Simultaneously, both variables explain 94.9% of the variation in interest in saving. Referring to these research findings, it can be confirmed that the integration of account officer service quality and loyalty strategies has a significant effect on strengthening the culture of saving and increasing the competitiveness of Islamic microfinance institutions